Modeling bacterial fate and transport for local catchments - Ong, Wei Jing. (2011)
This report describes the review and assessment of two commonly used runoff and water quality modeling tools, Soil and Water Assessment Tool (SWAT) and Storm Water Management Model (SWMM), to assess water quality impacts due to the buildup, fate and transport of bacteria from storm runoff during wet weather for the Kranji catchment. Based on the reviews, SWAT is chosen primarily due to the strengths of the SWAT bacteria component over SWMM. Comparing between both models, SWMM does not have a specialized function to directly model bacteria, where bacteria are modeled through the pollutant buildup and washoff process. Whereas for SWAT, it can be used to study more specialized processes of bacteria transport and has simultaneous assessment of bacteria that possesses different growth/die‐off characteristics, different rate constants and the ability to account for multiple point and/or nonpoint bacteria sources. The setup of the model then requires a lot of input data. The land use classes were obtained through the SWAT database while the soil classes were obtained from previous studies on soil types in Singapore. For the weather data, the weather generator is customized to generate various weather parameters using the weather data collected from NTU-maintained meteorological station in Kranji Reservoir.